Lucian Blaga between philosophy and dogmatics - Cășvean, Emanuel-Ioan (Journal for the study of religions and ideologies, 2020)
Review of Ioan Biriș, Lucian Blaga - Concepte dogmatice [Lucian Blaga - Dogmatic concepts], (Cluj-Napoca: Editura Școala Ardeleană, 2020).